Genetic and Environmental Overlap between Low Self-Control and Delinquency - Boisvert, Danielle (Journal of quantitative criminology, 2012)
Low self-control has emerged as a consistent and strong predictor of antisocial and delinquent behaviors. Using the twin subsample of the National Longitudinal Study of Adolescent Health (Add Health), genetic analyses were conducted to examine the genetic and environmental contributions to low self-control and offending as well as to their relationship with one another. The results revealed that low self-control and criminal behaviors are influenced by genetic and nonshared environmental factors with the effects of shared environmental factors being negligible. In addition, the co-variation between low self-control and criminal behaviors appears to be largely due to common genetic and nonshared environmental factors operating on both phenotypes. The implications of these findings on the current understanding of Gottfredson and Hirschi’s general theory of crime are discussed.